2019
DOI: 10.1111/dth.12983
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Oleogel‐S10: A triterpene preparation for the treatment of epidermolysis bullosa

Abstract: Epidermolysis bullosa (EB) is a group of rare heterogeneous, genetic disorders. Currently, there is no effective pharmacological or genetic therapy for all EB subtypes. Dry extract from birch bark and betulin upregulate some pro‐inflammatory mediators and downregulate others. The increase in pro‐inflammatory cytokines is temporary and attenuated over long‐term treatment. This inflammatory stimulus is thought to be prerequisite for a secondary anti‐inflammatory response. Dry extract from birch bark and its acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(72 reference statements)
0
11
1
Order By: Relevance
“…Results suggested that Oleogel-S10 significantly facilitated the healing of superficial partial thickness burn wounds and it was superior to Octenilin ® in terms of efficacy and tolerability. Oleogel-S10 was also clinically proven to be effective for epidermolysis bullosa by phase II and III trials, and the mechanism was to promote the re-epithelialization of wounds ( Schwieger-Briel et al, 2017 ; Kern et al, 2019 ; Schwieger-Briel et al, 2019 ).…”
Section: Commercially Available Products For Wound Healing Derived Fr...mentioning
confidence: 99%
“…Results suggested that Oleogel-S10 significantly facilitated the healing of superficial partial thickness burn wounds and it was superior to Octenilin ® in terms of efficacy and tolerability. Oleogel-S10 was also clinically proven to be effective for epidermolysis bullosa by phase II and III trials, and the mechanism was to promote the re-epithelialization of wounds ( Schwieger-Briel et al, 2017 ; Kern et al, 2019 ; Schwieger-Briel et al, 2019 ).…”
Section: Commercially Available Products For Wound Healing Derived Fr...mentioning
confidence: 99%
“…It acts irrespective of the underlying molecular pathology in EB. 61 Currently, preliminary results from a Phase III double-blind, randomized, placebo-controlled “EASE” trial (NCT03068780) are showing sustained wound closure benefits in recessive DEB patients.…”
Section: Managementmentioning
confidence: 99%
“…One aspiration in developing EB therapeutics is to identify a topical product that promotes wound healing in all types of EB, irrespective of the underlying molecular pathology. To that end, a triterpene extract in sunflower oil, oleogel-S10 (Amryt Pharma, Cambridge, USA), has been shown to promote wound healing through inflammation modulation, stimulation of keratinocyte migration and altered epidermal differentiation [144,145]. A prospective, placebo-controlled phase II trial in EB showed clinical improvements, in which five out of twelve treated wounds had faster reepithelialization as judged by two independent reviewers, while significance was not attained due to limited participant numbers [146].…”
Section: Oleogel-s10mentioning
confidence: 99%